Solve this please.....
Attachments:
![](https://hi-static.z-dn.net/files/d1c/b4418c3fd2c08ce179a0149665c65f2b.jpg)
Answers
Answered by
1
x-3=0
x=3
putting value of x in equation x^2-7x+12
(3)^2-7×3+12
9-21+12
-21+21=0
x^2-7x+12 ÷ x-3 we get x-4 as questient and 0 as remainder
x^2-7x+12=x-3 × (x-4)+0
x^2-7x+12=x^2-4x-3x+12
x^2-7x+12=x^2-7x+12
hope it helps please mark it as brainliest answer.............
x=3
putting value of x in equation x^2-7x+12
(3)^2-7×3+12
9-21+12
-21+21=0
x^2-7x+12 ÷ x-3 we get x-4 as questient and 0 as remainder
x^2-7x+12=x-3 × (x-4)+0
x^2-7x+12=x^2-4x-3x+12
x^2-7x+12=x^2-7x+12
hope it helps please mark it as brainliest answer.............
Namit1111:
pls mark it as brainliest answer
Answered by
1
This is correct answer.
Attachments:
![](https://hi-static.z-dn.net/files/de9/43ee0458546d8925f70123dd6d434aeb.jpg)
Similar questions